Motivasi Berprestasi dan Prokrastinasi Akademik pada Peserta didik - Yuniarti Yuniarti; Rici Kardo (Universitas Ahmad Dahlan, 2022)
Achievement Motivation and Academic Procrastination in StudentsThis study aims to examine the relationship between achievement motivation and academic procrastination in class XI students who study online at SMA Negeri X. This research uses a quantitative method. The sampling technique used was accidental sampling. The scale used is the achievement motivation scale and the academic procrastination scale. Analysis of research data using Pearson Product Moment correlation. The results of data analysis obtained a correlation of -0.826 (r=-0.826) with a significance level of p=0.000 (p<0.01). This shows that there is a very significant negative relationship between achievement motivation and academic procrastination. The effective contribution of the achievement motivation variable to academic procrastination is 68.3%. Based on the results above, it is concluded that there is a relationship between achievement motivation and academic procrastination in students. This means that the higher the achievement motivation, the lower the academic procrastination. Conversely, if the lower the achievement motivation, the higher the academic procrastination of students.